1986
DOI: 10.1063/1.97334
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise in low 1/f noise dc SQUID’s

Abstract: We demonstrate that the low-frequency noise in our edge junction dc superconducting quantum interference devices, with a basic 1/f flux noise of 2×10−12 Φ20/Hz at 1 Hz, can all be accounted for in terms of junction critical current fluctuations. A novel modulation readout scheme is able to cancel the effect of junction critical current fluctuations and reduce our total noise to 1×10−12 Φ20/Hz at 0.1 Hz, a level that is three times lower than the lowest flux noise ever previously reported at this frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 9 publications
2
36
0
Order By: Relevance
“…1/f noise in the critical current of Josephson junctions has been observed experimentally [41,42,43,44]. The microscopic source of this noise is unknown, though it has been suggested that the tunneling of atoms or ions is involved [16].…”
Section: −1mentioning
confidence: 99%
“…1/f noise in the critical current of Josephson junctions has been observed experimentally [41,42,43,44]. The microscopic source of this noise is unknown, though it has been suggested that the tunneling of atoms or ions is involved [16].…”
Section: −1mentioning
confidence: 99%
“…These workers also were able to reduce the 1/f noise in the system using a modified version of the modulation scheme of Foglietti ~&. 39 Although.they need further development, cryogenic digital feedback schemes offer several advantages: they are compact, produce a digitized output for transmission to room temperature, offer wide flux-locked bandwidths, and need not add any noise to the intrinsic noise of the SQUID.…”
Section: G Alternate Read-out Schemesmentioning
confidence: 99%
“…• An alternate scheme, second harmonic detection (SHAD), has recently been developed by Foglietti et al 39 , and we shall briefly describe it. In Fig.…”
mentioning
confidence: 99%
“…The l/f flux noise S Φ 1/2 (1 Hz) was within a factor of 3 of 10 μΦ 0 Hz -1/2 for Nb-or Pb-based SQUIDs at 4.2 K, even though the loop areas ranged over 6 orders of magnitude; here, Φ denotes magnetic flux and Φ 0 ≡ h/2e is the flux quantum. Subsequently, other authors found rather lower levels of l/f flux noise at 1 Hz and 4.2 K, for example, 0.5 μΦ 0 Hz -1/2 [2] and 0.2 μΦ 0 Hz -1/2 [3]. Wellstood et al [4] reported values of S Φ 1/2 (1 Hz) of (4-10) μΦ 0 Hz -1/2 at temperatures below 0.1 K in 12 Nb, Pb and PbIn devices.…”
mentioning
confidence: 99%